EFEKTIVITAS EKSTRAK DAUN JAMBU METE (Anacardium Occidentale L) TERHADAP PERTUMBUHAN Aggregatibacter Actinomycetemcomitans PADA GINGIVITIS - In Vitro - Nendika Dyah Ayu; Recita Indraswary; Sandy Christiono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Aggregatibacter actinomycetemcomitans found in plaque that will be the primary cause of gingivitis. Extract of Anacardium occidentale L leaves contains antibacterial substances which can help to preserve the health of the teeth. This research purposed to ensure the effectiveness of antibacterial effect in extract of Anacardium occidentale L leaves to Aggregatibacter actinomycetemcomitans growth in gingivitis. Method: The research was conducted using the extract of Anacardium occidentale L leaves concentration of 5%, 16%, 32%, 40%, 60%, 80%,96%, aquades as control negative, metronidazole as control positive. The making extracts of Anacardium occidentale L leaves was done by maceration method. And then the extract tested by sinks diffusion method, one petri disk have a sink, with 3 times repetition, incubated for 24 hours and measured its radical zone with a caliper. Result: The radical zone average of Anacardium occidentale L leaves extract concentration of 5%, 16%, 32%, 40%, 60%, 80%, 96% respectively is 4.47 mm, 12.04 mm, 5.80 mm, 6.55 mm, 6.85 mm,7.20 mm, 8.05 mm. There were differences with One Way Anova in the groups treated with significance of 0.000. Conclusion: According to the research concluded that there is antibacterial potency in extract of Anacardium occidentale L leaves to bacterial growth of Aggregatibacter actinomycetemcomitans.